Biografi Nabi Muhammad SAW Dalam Sejarah Perspektif Karen Armstrong - Umi Wasilatul Firdausiyah (Universitas Islam Negeri Imam Bonjol Padang, 2020)
The discourse of this study is about the views of an orientalist, Karen Armstrong, in describing the figure of the Prophet Muhammad by looking at the texts and methods used by Armstrong, and the purpose of this study is to explore Armstrong's understanding of the figure of Muhammad who is actually a role model for Muslims. This study was conducted using a qualitative approach with the type of research in the form of Library Research, accompanied by documentation data collection techniques and methods using historical analytical-descriptive type as a bridge to explain Armstrong's thoughts about the Prophet Muhammad, accompanied by a sociological approach to knowledge and the theory used is effective intellectual heremeneutics. from Gadamer. The results of this paper are related to Armstrong's objective interpretation that Muhammad was an extraordinary figure who had a major influence on the change of the Arabs and Armstrong's text study uses a critical-historical method with an empathetic approach. Armstrong explained the figure of Muhammad, because according to him it is important to be done to improve the history of Islam and the middle east